Gravitational waves from mountains in newly born millisecond magnetars. Issue 4 (4th February 2021) - Sur, Ankan; Haskell, Brynmor
ABSTRACT: In this paper, we study the spin-evolution and gravitational-wave luminosity of a newly born millisecond magnetar, formed either after the collapse of a massive star or after the merger of two neutron stars. In both cases, we consider the effect of fallback accretion; and consider the evolution of the system due to the different torques acting on the star, namely the spin-up torque due to accretion and spin-down torques due to magnetic dipole radiation, neutrino emission, and gravitational-wave emission linked to the formation of a 'mountain' on the accretion poles. Initially, the spin period is mostly affected by the dipole radiation, but at later times, accretion spin the star up rapidly. We find that a magnetar formed after the collapse of a massive star can accrete up to 1 M⊙, and survive on the order of 50 s before collapsing to a black hole. The gravitational-wave strain, for an object located at 1 Mpc, is hc ∼ 10 −23 at kHz frequencies, making this a potential target for next-generation ground-based detectors. A magnetar formed after a binary neutron star merger, on the other hand, accretes at the most 0.2 M⊙ and emits gravitational waves with a lower maximum strain of the order of hc ∼ 10 −24, but also survives for much longer times, and may possibly be associated with the X-ray plateau observed in the light curve of a number of short gamma-ray burst.